2015
DOI: 10.1111/jcpp.12445
|View full text |Cite
|
Sign up to set email alerts
|

Callous‐unemotional traits and impulsivity: distinct longitudinal relations with mind‐mindedness and understanding of others

Abstract: BackgroundProblems in understanding other people's mental states may relate to distinct personality traits that are associated with early externalizing behavior. A distinction between theory of mind (ToM) and empathy has proven important in shedding light on the problems in understanding other minds encountered by children high on callous‐unemotional (CU) traits and exhibiting impulsivity. The aim of this study was to investigate whether children's early ToM and emotion understanding abilities predicted CU tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 39 publications
(44 reference statements)
7
56
0
2
Order By: Relevance
“…Maternal mind‐mindedness has been shown to predict various positive aspects of children's development, including attachment security (e.g., Arnott & Meins, ; Laranjo, Bernier, & Meins, ; Lundy, ; Meins et al., , ), executive abilities (Bernier, Carlson, & Whipple, ; Bernier, McMahon, & Perrier, ), early language abilities (Bernier et al., ; Meins, Fernyhough, Arnott, Leekam, & de Rosnay, ), theory of mind (Kirk et al., ; Laranjo, Bernier, Meins, & Carlson, , ; Meins et al., ), emotion understanding (Centifanti, Meins, & Fernyhough, ), and in children from low socioeconomic status backgrounds fewer behavioral difficulties (Meins, Centifanti, Fernyhough, & Fishburn, ) and higher school attainment (Meins, Fernyhough, & Centifanti, ).…”
mentioning
confidence: 99%
“…Maternal mind‐mindedness has been shown to predict various positive aspects of children's development, including attachment security (e.g., Arnott & Meins, ; Laranjo, Bernier, & Meins, ; Lundy, ; Meins et al., , ), executive abilities (Bernier, Carlson, & Whipple, ; Bernier, McMahon, & Perrier, ), early language abilities (Bernier et al., ; Meins, Fernyhough, Arnott, Leekam, & de Rosnay, ), theory of mind (Kirk et al., ; Laranjo, Bernier, Meins, & Carlson, , ; Meins et al., ), emotion understanding (Centifanti, Meins, & Fernyhough, ), and in children from low socioeconomic status backgrounds fewer behavioral difficulties (Meins, Centifanti, Fernyhough, & Fishburn, ) and higher school attainment (Meins, Fernyhough, & Centifanti, ).…”
mentioning
confidence: 99%
“…Early mind‐mindedness is also positively related to children's sociocognitive development throughout early childhood. For example, mothers' appropriate mind‐related comments in the 1st year of life predict superior theory‐of‐mind abilities between ages 2 and 4 (Laranjo, Bernier, Meins, & Carlson, , ; Meins, Fernyhough, Arnott, Leekam, & de Rosnay, ; Meins et al., , ) and better age‐4 emotion understanding (Centifanti, Meins, & Fernyhough, ). Research has so far failed to identify mediating factors in the relation between early appropriate mind‐related comments and children's later mentalizing abilities.…”
mentioning
confidence: 99%
“…Using an index of parental sensitivity derived from parent–child observations at ages 24, 36, and 58 months, Wagner, Mills‐Koonce, Willoughby, Zvara, and Cox () found that less sensitive parenting predicted higher levels of CU traits in first grade controlling for earlier measures of CU behaviors. We have previously reported that maternal sensitivity assessed at age 29 weeks predicted CU traits at 2.5 years (Bedford, Pickles, Sharp, Wright, & Hill, ), and Centifanti, Meins, and Fernyhough () found that mind‐mindedness, indexing the mother's awareness of her infant's states of mind, assessed at age 8 months predicted children's self‐report of CU traits at 10 years.…”
Section: Introductionmentioning
confidence: 96%